The Contribution of Western Movies as Media for EFL Students to Learn English in the Classroom - Warahmah, Mawaddah (Indonesian Journal of Integrated English Language Teaching, 2024)
Nowadays, media becomes crucial aspect in language learning and teaching, since the rapid of technology in this world.  This study aimed to review some previous studies about the use of western movies as media for EFL students in language classroom.  To give sight for teachers that using media in the classroom can assist students to improve their language skills. The study is a library research study which was conducted by reviewing several library works that are relevant and related based on existing problems. Around 15 studies related to this topic were discussed. The data were analyzed using two different thought processes, such as inductive and deductive. Deductive analysis was a method of thinking to draw findings using reasoning starting from general statements to particular inquiries, whereas inductive analysis was a way of thinking to draw conclusions starting from specific facts to general conclusions. It is found that using movies as media in language learning can improve students’ English language skill in idiomatic expression, vocabulary, and speaking.